Estudo das relações da variabilidade climatológica relacionada à variabilidade social da safra de pescados de água doce desembarcado na cidade do Rio Grande RS - Clavico, Leandro Sampaio (2009)
In this study the south area of the State of Rio Grande do Sul was chosen, to study the possible relationship of climatological variables with the fish disembarkation, seeking to explore the possibility to include contributions of these varied in the models of administration of the stocks of fish of fresh water of the area included by the Pond of the Ducks and Little Pond. For this, it was used the data of fish disembarkation in the city of Rio Grande, during the years of 1987 and 2006 originating from of embarkations of the cities of São Lourenço do Sul, Pelotas, Rio Grande, São José do Norte and Santa Vitória do Palmar, systematically they are organized for IBAMA / CEPERG (Center of Research and Administration of the Fishing Resources Lagunares and Estuarinos ). The climatological data were obtained in the site http//www.cdc.noaa.gov/cdc (NOAA). Starting from the analysis of the data of fish disembarkation it was observed that the fish specimens Jundiá and Traíra act more of the half of all the captured production and disembarked in Porto of Rio Grande/RS city inside of the period study. It was calculated the averages trimestrais of disembarkation of fish of the specimens Jundiá and Traíra for the four quarters of every year. Starting from the analysis of the data, identified that the third quarter is the most significant in the requirement amount (kg) of disembarkation for the specimen jundiá , while for the specimen Traíra was the second quarter. Starting from the statistical analyses correlating fish disembarkation and climatological variables was verified that for the specimen Jundiá the more significant climatological variables for it quarter of larger importance were: for the month of component July V of the wind, rain and long wave radiation (LWR), for the month of August already, component U of the wind, temperature and (LWR) and, consequently, for the month of September the most significant variables are component U and V of the wind and speed of the wind. And for the specimen Traíra the climatological variables that obtained larger significance indexes for more expressive quarter were: for the month of component April V of the wind and temperature, for the month of May already, all the variables present important values for analysis, in other words, component variable U and V of the wind, speed, temperature, rain and long wave radiation (LWR) and, consequently, for the month of June the more significant climatological variables are component U of the wind, speed of the wind and rain.